Pengaruh Pendidikan Kewirausahaan Dan Motivasi Berwirausaha Terhadap Minat Berwirausaha Pada Siswa SMK Patria Gadingrejo, Pringsewu - Hesti Yulistiani; Rini Loliyani; Umar Bakti (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2023)
Planting entrepreneurship education and entrepreneurial motivation in growing interest in entrepreneurship for vocational students is an important aspect in producing graduates who are able to create jobs (entrepreneurship). This research is a type of descriptive quantitative research, the sample in this study is as many as 60 respondents. With the results of the study it was found that the variable entrepreneurship and entrepreneurial motivation have a positive influence on interest entrepreneurship education. Taken together, the influence of entrepreneurship education (X1) and entrepreneurial motivation (X2) has an influence with a percentage of 83,9%. While the remaining 16,1% is influenced by other variables not examined by researchers.